On the Crucial Role of Isolated Electronic States in the Thermal Reaction of ReC(+) with Dihydrogen - Li, Jilai (Angew Chem Int Ed Engl, 2020)
Presented here is that isolated, long‐lived electronic states of ReC(+) serve as the root cause for distinctly different reactivities of this diatomic ion in the thermal activation of dihydrogen. Detailed high‐level quantum chemical calculations support the experimental findings obtained in the highly diluted gas phase using FT‐ICR mass spectrometry. The origin for the existence of these long‐lived excited electronic states and the resulting implications for the varying mechanisms of dihydrogen splitting are addressed.